Advanced introduction to freedom of expression - Tushnet, Mark V. (Cheltenham Edward Elgar Publishing, 2018)
Mark Tushnet presents a concise yet comprehensive overview of free expression law, understood as a form of constitutional law. Confronting the major issues of free expression - speech critical of government, libel law, hate speech regulation, and the emerging challenges posed by new technologies - he evaluates the key questions and potential difficulties for future generations. Contrasting the United States with current law in Europe and elsewhere, Tushnet argues that freedom of expression around the world should reflect deference to legislative judgements, unless those judgements reflect inadequate deliberation or bias, and that much of the existing free expression law is consistent with this view. Key features include: Comprehensible for both students of law and non-specialist readers interested in freedom of expression from a legal perspective; Viewpoints from multiple legal systems including analysis of decisions made by the US Supreme Court and the European Court of Human Rights; Explains the two legal doctrinal structures: categorical, rule-bound approaches and standards-based approaches; List of key references for further reading, allowing readers to extend their knowledge of the topic past the advanced introduction. This Advanced Introduction will be an essential foundational text for students of law, as well as those from a political science background who can view freedom of expression from a legal perspective.
Includes bibliographical references and index.
Keywords: Freedom of expression